Effect of maritime training and human factors on oil pollution violations - Rajoo, Balaji (Fakulti Pengajian Maritim dan Sains Marin, 2011)
Ship operations have been a source of marine pollution. Of various pollutions, oil pollution has caused serious long and short term harm. Maritime training addresses the concerns by disseminating knowledge of relevant machinery operations and regulations. The control measures include heavy penalties and in the recent past have resulted in criminalisation of the seafarers. In spite of this, incidents of oil pollution and falsifying records to prove compliance have been occurring.